"Replace them by Salads and Vegetables": Dietary Innovation, Youthfulness, and Authority, 1900–1939. Issue 2 (3rd July 2018) - Stark, James F.
ABSTRACT: The events of the First World War fueled public fascination with rejuvenation at the same time as medical scientists began to explore the physiological potential of so-called "vitamine." The seemingly bottomless capacity of vitamins to maintain bodily function and appearance offered a possible mechanism for achieving bodily renewal, alongside established dietary practices such as abstention from alcohol and meat. Drawing on mainstream medical publications, popular dietary texts and advertising materials, this paper outlines how vitamins and other dietary practices played an important but hitherto unrecognized role in reconfiguring ideas about anti-aging and rejuvenation. I argue that new ways of understanding food and its relationship with the body were at the heart of attempts by various groups to claim expertise about and authority over diet and its effects, not just on the human body in general, but on the aging process in particular.